2021
DOI: 10.1038/s41419-021-04150-4
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic secretion of HMGB1 from cancer-associated fibroblasts promotes metastatic potential of non-small cell lung cancer cells via NFκB signaling

Abstract: Tumor progression requires the communication between tumor cells and tumor microenvironment (TME). Cancer-associated fibroblasts (CAFs) are major components of stromal cells. CAFs contribute to metastasis process through direct or indirect interaction with tumor cells; however, the underlying mechanism is largely unknown. Here, we reported that autophagy was upregulated in lung cancer-associated CAFs compared to normal fibroblasts (NFs), and autophagy was responsible for the promoting effect of CAFs on non-sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 40 publications
(51 reference statements)
1
33
0
Order By: Relevance
“…The SCNAs of four subtypes in the TCGA-BLCA cohort were analyzed and compared, and the result showed that the four subtypes had different SCNAs ( Figure 6A ). The 13q12.3 amplification in C1 contained HMGB1, which could promote the development of MDSC and the metastasis of cancer cells ( Gorgulho et al, 2019 ; Ren et al, 2021 ). FSCN1 amplification at 7p22.1, Gab2 amplification at 11q14.1, and CD44 amplification at 11p13 were also associated with promoting tumor invasion ( Ke et al, 2007 ; Li et al, 2018 ; Rohani et al, 2019 ) and inducing tumor resistance to radiotherapy ( Li et al, 2021 ), suggesting that patients with C1 had high immune suppression, active EMT, and may not be suitable for radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The SCNAs of four subtypes in the TCGA-BLCA cohort were analyzed and compared, and the result showed that the four subtypes had different SCNAs ( Figure 6A ). The 13q12.3 amplification in C1 contained HMGB1, which could promote the development of MDSC and the metastasis of cancer cells ( Gorgulho et al, 2019 ; Ren et al, 2021 ). FSCN1 amplification at 7p22.1, Gab2 amplification at 11q14.1, and CD44 amplification at 11p13 were also associated with promoting tumor invasion ( Ke et al, 2007 ; Li et al, 2018 ; Rohani et al, 2019 ) and inducing tumor resistance to radiotherapy ( Li et al, 2021 ), suggesting that patients with C1 had high immune suppression, active EMT, and may not be suitable for radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…HMGB1 plays a significant role in many diseases, including autoimmune diseases, infectious diseases, inflammatory diseases, and cancer ( Kang et al, 2013 ; Tripathi et al, 2019 ). In cancer, HMGB1 plays dual roles as both a pro-cancer and an anti-cancer factor by regulating multiple cellular processes, including proliferation, angiogenesis, and invasion ( Wu et al, 2018 ; Ren et al, 2021 ). HMGB1 has been shown to enhance tumor growth, angiogenesis, and metastasis of a variety of cancers, including breast cancer, prostate cancer, colorectal cancer, and lung cancer ( Zhang J et al, 2014 ; Zhang L et al, 2014 ; Meng et al, 2014 ; Süren et al, 2014 ; Liu et al, 2015 ; Sun et al, 2015 ; Ren et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, HMGB1 plays dual roles as both a pro-cancer and an anti-cancer factor by regulating multiple cellular processes, including proliferation, angiogenesis, and invasion ( Wu et al, 2018 ; Ren et al, 2021 ). HMGB1 has been shown to enhance tumor growth, angiogenesis, and metastasis of a variety of cancers, including breast cancer, prostate cancer, colorectal cancer, and lung cancer ( Zhang J et al, 2014 ; Zhang L et al, 2014 ; Meng et al, 2014 ; Süren et al, 2014 ; Liu et al, 2015 ; Sun et al, 2015 ; Ren et al, 2021 ). In contrast, Kang et al (2013) and Luan et al (2017) reported that HMGB1 acts as a tumor suppressor in pancreatic cancer and endometrial carcinoma ( Tang et al, 2010 ; Zuo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 plays a significant role in many diseases, including autoimmune diseases, infectious diseases, inflammatory diseases, and cancer (Kang et al, 2013;Tripathi et al, 2019). In cancer, HMGB1 plays dual roles as both a pro-cancer and an anti-cancer factor by regulating multiple cellular processes, including proliferation, angiogenesis, and invasion (Wu et al, 2018;Ren et al, 2021). HMGB1 has been shown to enhance tumor growth, angiogenesis, and metastasis of a variety of cancers, including breast cancer, prostate cancer, colorectal cancer, and lung cancer Zhang L et al, 2014;Meng et al, 2014;Süren et al, 2014;Liu et al, 2015;Sun et al, 2015;Ren et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…In cancer, HMGB1 plays dual roles as both a pro-cancer and an anti-cancer factor by regulating multiple cellular processes, including proliferation, angiogenesis, and invasion (Wu et al, 2018;Ren et al, 2021). HMGB1 has been shown to enhance tumor growth, angiogenesis, and metastasis of a variety of cancers, including breast cancer, prostate cancer, colorectal cancer, and lung cancer Zhang L et al, 2014;Meng et al, 2014;Süren et al, 2014;Liu et al, 2015;Sun et al, 2015;Ren et al, 2021). In contrast, Kang et al (2013) and Luan et al (2017) reported that HMGB1 acts as a tumor suppressor in pancreatic cancer and endometrial carcinoma (Tang et al, 2010;Zuo et al, 2014).…”
Section: Figurementioning
confidence: 99%